Playing bluegrass in Australia across country and folk scenes - Jones, Miriam (Perfect Beat, 2017)
Bluegrass music has attracted Australian musicians and audiences since the 1960s. The popularity of hillbilly music in Australia from the 1930s onwards meant that Australian musicians were primed to engage with and appropriate the aesthetically related sounds of bluegrass. Because of its niche status, bluegrass has found musical homes across larger Australian folk and country scenes. In turn, the internal logics, ideologies and institutional structures of these two scenes have shaped Australian bluegrass musicians’ musical practices. Oral histories of key figures in the history and institutionalization of bluegrass in Australia illuminate the ways in which musicians have engaged with bluegrass across folk and country scenes.